2021
DOI: 10.1177/21649561211001038
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Yoga-Based Mind-Body Intervention for Resident Physicians: A Randomized Clinical Trial

Abstract: Background and Objective Mind-body interventions (MBIs) have been shown to be effective individual-level interventions for mitigating physician burnout, but there are no controlled studies of yoga-based MBIs in resident physicians. We assessed the feasibility of a yoga-based MBI called RISE (resilience, integration, self-awareness, engagement) for residents among multiple specialties and academic medical centers. Methods We conducted a waitlist controlled randomized clinical trial of the RISE program with resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 63 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…A significant increase in resilience was found between pre-test and follow up. Consistent with the present results, a short-term increase in resilience was found among forty-four participants who engaged in six weekly mind-body intervention sessions [ 34 ]. Similarly, a study found that after engaging in a 9 week mind-body intervention, 279 students showed a significant increase in resilience and mindfulness, compared to 247 students who did not engage in the intervention [ 35 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A significant increase in resilience was found between pre-test and follow up. Consistent with the present results, a short-term increase in resilience was found among forty-four participants who engaged in six weekly mind-body intervention sessions [ 34 ]. Similarly, a study found that after engaging in a 9 week mind-body intervention, 279 students showed a significant increase in resilience and mindfulness, compared to 247 students who did not engage in the intervention [ 35 ].…”
Section: Discussionsupporting
confidence: 89%
“…It is worth noting that one advantage of the WeActive and WeMindful intervention programs was their virtual delivery. Participants in Lowenthal et al expressed that virtual delivery would have increased conveniency for busy individuals, possibly by cutting down on travel time [ 34 ]. The participants in the WeActive and WeMindful groups had the added benefit of the second weekly session to be asynchronous.…”
Section: Discussionmentioning
confidence: 99%
“…But it can also be the effect of protective factors such as having more time to spend on reading/didactics, hobbies, or family/significant others due the reduction in usual clinical work or taking advantage of this period to carry out scientific work ( 28 , 34 ). Either way, the pandemic situation has highlighted the importance of implementing wellness programs in institutions and their maintenance during times of health crisis ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have described improvement in symptoms of burnout, musculoskeletal pain, and psychological well-being among health-care workers, as well as demonstrating the feasibility of habitual yoga practice within a workday. [ 23 24 25 26 27 28 ] For example, Babbar et al . describe outcomes of a yoga-based initiative among resident physicians and report significantly reduced feelings of depersonalization (a common symptom of burnout), increased feelings of camaraderie and motivation, improved quality and duration of sleep, as well as significant reductions in blood pressure compared to peer nonparticipants.…”
Section: Benefits Of Yoga To Practicing Surgeonsmentioning
confidence: 99%
“…encourage the availability of virtually guided yoga as a method of increasing participation and adherence among busy resident physicians. [ 25 ]…”
Section: Benefits Of Yoga To Practicing Surgeonsmentioning
confidence: 99%